IMPLEMENTATION OF HINDU RELIGION EDUCATION AT ELEMENTARY SCHOOL IN THE PERSPECTIVE OF CULTURAL STUDIES - Tanu, I Ketut; Suastika, I Made; Parimartha, I Gde; Subagia, I Wayan (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2009)
Religious education was firstly implemented based on the Act of Number 4 year1950, concerning education and teaching. In one of its articles, it is stated that Indonesia is areligion-based country. The govern ment has the right and is obliged to arrange religiouseducation starting from Kindergarten to University and the time allocated for this is 2 (two)hours per week. However, an imbalance has occurred as far as Hindu Religion education isconcerned, that is, the students at particular educational institutions are not provided withHindu Religion education as intended by the Act.In Article 30 of the Act of Number 20 year 2003 concerning national educationsystem, on the other hand, it is stated that: any religious education can be carried out by thegovernment and or a community’s group belonging to a particular religion in accordancewith the applicable regulations. It is also stated that religious education is functioned toprepare the students to be able to comprehend and apply their religious teaching values and orto be experts in religions. In addition, it is also stated that religious education can be formallyand informally conducted in the forms of diniyah, pesantren, pesraman, phabaja, smnera,and the like.How Hindu Religion educa tion is implemented at Elementary School Number 17Dauh Puri and Dwijendra Elementary School Depasar cannot be separated from theinfrastructure, facilities, curri culum and teachers available, and the government’s policy.Therefore, this study is focused on 1) the existence of the components needed forimplementing Hindu Religion education, 2) the factors influencing the implementation ofHindu religion education, and 3) the meaningfulness and attempts done to implement HinduReligion education if related to the inventory of Balinese culture.This study is conducted to explain, describe, criticize, and analyze theimplementation of Hindu Religion education at Elementary School Number 17 Dauh Puri andDwijendra Elementary School Denpasar. The benefit that is intended to be achieved in thisstudy is to contribute to the inventory of Hinduism and to serve as something to be taken intoaccount when any decision related to Hindu Religion education is made.Researches on Hinduism have been conducted by some researchers. However, onlya few have been carried out related to Hindu Religion education. Further matters related toHindu Religion education provided at elementary school need to be done. The concepts madeavailable in this study are very essential. The reason is that such concepts serve as theguidelines in this study. The concepts employed are those related to the implementation ofeducation, general education, Hindu Religion education, Elementary School, and culturalstudies.The theories employed to answer the matters related to the implementation of HinduReligion education at Elementary School Number 17 Dauh Puri and Dwijendra Elementary School Depasar are: 1) the Derida’s theory of deconstruction, 2) Gramsci’s theory ofHegemony, and 3) Piaget’s constructivistic theory. In addition, a research model is alsoemployed in this study. The reason is that it serves as the researcher’s thinking flow indescribing and reporting the research.The methods employed in this study include the research planning, the researchlocation, the types and sources of data, the informant determination, the researchinstruments, the data collecting technique, the data analysis, and how the results arepresented. The purpose is to obtain objective data concerning the implementation of HinduReligion education at elementary school. The objective research method is able to describetotally and objectively how Hindu Religion education is implemented at Elementary SchoolNumber 17 Dauh Puri and Dwijendara Elementary School Denpasar.The novelty in this study is that the learning infrastructure and facilities needed tocarry out Hindu Religion education both at Elementary School Number 17 Dauh Puri andDwijendra Elementary School Depasar have not been in accordance with the minimumstandard of service , that the curriculum has not been totally oriented towards the schools’potentials and students, that the teachers have not been innovated in the learning process, andthat the government’s policy has not been made for multicultural education. In the process oflearning Hindu Religion, the schools have attempted to increase the quality of Hindu Religioneducation, to develop school-based management, and to apply multidisciplinary approach.